PENGGUNAAN TEKNOLOGI NANO UNTUK MENGHASILKAN FILTER AIR BERSIH BAGI MASYARAKAT PERAIRAN KABUPATEN BANYUASIN - Ida Sriyanti; Leni Marlina; Muhammad Rudi Sanjaya; Muhammad Rama Almafie; Jaidan Jauhari (Universitas Negeri Medan, 2022)
One of the communities in the waters of Air Kumbang District, Banyuasin Regency, South Sumatra Province is Sido Makmur Village. Due to its location near the high tide, where the water is foggy, rusty and acidic, people in the region are currently facing challenges in getting clean water. The implementation of this service was carried out on August 23, 2021 and September 19, 2021, which was carried out offline in the prosperous Sido Village, which was attended by 25 participants. Meanwhile, follow-up activities are carried out online. The implementation of this activity uses a mentoring approach to achieve the goals that have been set. Through the village head, the residents of Sido Makmur Village asked for assistance from lecturers of the Masters Study Program (S2) Physics Education FKIP, Fasilkom, and LPPM Universitas Sriwijaya in order to provide training and information on water purification technology based on nanofiber membranes. as a new solution to the problems faced by the people of Sido Makmur Village who are currently facing a crisis. pure water. The results showed that the people of Sido Makmur Village were very satisfied and benefited from the service related to the importance of using clean water and water filters, especially the use of nano fiber filters as a solution that the proposing team offered to help solve the problem of difficult access to clean water in the village. This shows that the dedication carried out by the proposing team has succeeded in helping to solve the problem of difficulty in accessing clean water in the village, through education on the water filter system.Penggunaan Teknologi Nano untuk Menghasilkan Filter Air Bersih Bagi Masyarakat Perairan Kabupaten Banyuasin